The impact of foreign aid on gender inequality in developing countries: Does it really work? - Vimala Asty F.T. Jaya; Jaehyun Jung; Jinhwan Oh (Global Business & Finance Review (GBFR), 2024)
Purpose: This study examines how foreign aid affects gender inequality in developing countries, both at macro (overall) and micro (sectoral) levels. Design/methodology/approach: This study uses comprehensive panel data between 2010 and 2019. Findings: The major findings are: (1) foreign aid, particularly aid targeting women empowerment and gender equal-ity, has significantly contributed to the improvement of gender equality at the macro level except for the least developed countries, (2) at the micro level, gender-targeted aid has significantly improved the share of women in parliament and female secondary education, and (3) the availability of gender mainstreaming policies and national mechanisms for gender equality have not significantly contributed in improving gender equality. Research limitations/implications: These findings suggest that, while donor countries should keep expanding gen-der-targeted foreign aid in developing countries, it would be crucial to improve the performance of national mecha-nisms for gender equality as well as gender mainstreaming policies in developing countries. Originality/value: Studies have examined how foreign aid impacted gender inequality, but none of them has used gender-specific aid for an empirical approach, which is a main contribution of this study.
Keywords: 650; Foreign aid; Gender inequality; Women empowerment; Gender mainstreaming